Synthesis and Characterization of Cationic Surfactant Cobalt(III) Complexes Containing 3,8-Dimethyl-5,6-Benzo-4,7-Diaza Deca-3,7-diene-2,9-dione Dioxime - ARUMUGHAM, M.N.; SANTHAKUMAR, K.; ARUNACHALAM, S. (Asian Journal of Chemistry, 2012)
A number of mixed ligand complexes of the type trans-[Co(DODOHbzo)(AM)(X)](ClO4)2 and [Co(DODOHbzo)(AM)2(ClO4)2 where (DODOHbzo = mono anion of 3,8-dimethyl-5,6-benzo-4,7-diaza deca-3,7-diene-2,9-dioxime, AM = propylamine or dodecylamine and X = Cl– or I–) have been synthesized and characterized. The electronic absorption spectra, IR and NMR (1H) spectra indicate the trans configuration for the isolated complexes.